TAKHBIB (REACHING THE LOVE OF A HUSBAND WOMAN) PERSPECTIVE OF IMAM IBNU KATSIR AND QURAISH SHIHAB - Nursiah, Nursiah; Sulidar, Sulidar (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
The rise of cases of perpetrators and perpetrators in social networks has made researchers try to examine what causes these cases to occur. And how does the view of Islamic law respond to the case. Until the term takhbib arose in Islam. Until it is known that takhbib is an act of seducing one of the legitimate married couples by inviting them to commit adultery, both adultery of the eyes, hands and heart to the point of genital adultery so that the husband or wife hates their legal husband or wife